The Role of Intraoperative Radiotherapy Treatment of Locally Advanced Rectal Cancer - Amarnath, Sudha R. (Clinics in Colon and Rectal Surgery, 2023)
Intraoperative radiation therapy (IORT) has been used in the treatment of locally advanced and recurrent rectal cancers for the last several decades. Given the heterogeneity of patients treated and different indications for use and dosing at different institutions, it has been difficult to discern if IORT adds any appreciable benefit to standard of care therapies. Herein, the rationale for IORT in rectal cancer is discussed along with the most modern and best available data in 2023. IORT is likely indicated in patients with locally advanced and locally recurrent rectal cancer with threatened margins (R0 or R1 resection) to help improve local control. High-quality imaging and multidisciplinary discussion are necessary to ensure optimal patient selection. Appropriate counseling of the patient and excellent team communication are of the utmost importance given the challenging nature of these cases and the prognostic implications of R1 and R2 resections in this patient population.
Keywords: intraoperative radiotherapy; intraoperative radiation therapy; rectal cancer